2018
DOI: 10.1177/1369433218787714
|View full text |Cite
|
Sign up to set email alerts
|

Study of the residual axial capacities of shear-damaged reinforced concrete columns: Part 1—development of an evaluation model

Abstract: This is the first of two companion papers addressing the residual axial capacities of shear-damaged reinforced concrete columns. To evaluate the residual axial capacity, this article presents an arch resistance model that is based on the theory of mechanics and can reasonably explain the collapse mechanism of shear-damaged reinforced concrete columns. In the proposed model, the residual axial capacity of the column is evaluated by considering the interaction between the contributions of the longitudinal bars a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In part 1 (Yang et al, 2018) of the companion papers, it is confirmed that the proposed model can accurately evaluate the residual axial capacities of the columns with transverse reinforcements ratio of less than 5%; however, for the columns with transverse reinforcement ratios of greater than 5%, the proposed model overestimates the residual axial capacities. The reason is believed to be related to the assumption that transverse reinforcements within the shear-damaged region can fully develop their strength at axial collapse.…”
Section: Experimental Programmentioning
confidence: 74%
See 2 more Smart Citations
“…In part 1 (Yang et al, 2018) of the companion papers, it is confirmed that the proposed model can accurately evaluate the residual axial capacities of the columns with transverse reinforcements ratio of less than 5%; however, for the columns with transverse reinforcement ratios of greater than 5%, the proposed model overestimates the residual axial capacities. The reason is believed to be related to the assumption that transverse reinforcements within the shear-damaged region can fully develop their strength at axial collapse.…”
Section: Experimental Programmentioning
confidence: 74%
“…One is to obtain the experimental results of stress state of transverse reinforcements to investigate the applicable scope of the proposed model; the other is to obtain the experimental results of the axial forces carried by the longitudinal bars and concrete core to further verify the accuracy of the proposed model. Based on the experimental database in part 1 (Yang et al, 2018) of this study, the specimens are designed with different transverse reinforcement and axial load ratios.…”
Section: Experimental Programmentioning
confidence: 99%
See 1 more Smart Citation